2015
DOI: 10.1186/s12906-015-0949-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiviral activity against rotavirus and astrovirus infection exerted by substances obtained from Achyrocline bogotensis (Kunth) DC. (Compositae)

Abstract: BackgroundAchyrocline bogotensis has been traditionally used to treat infections of skin, respiratory, tract urinary and other infections, but not to treat viral gastrointestinal disease. In this study, this Colombian native medicinal plant was investigated by its in vitro anti-rotavirus and anti-astrovirus activity.MethodsSeveral extracts and fractions phytochemically obtained from A. bogotensis were evaluated initially for their cell toxicity on MA104 and Caco2 cells and then for their anti-rotavirus (RRV) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…Several recent studies demonstrate that plant extracts are deeply explored for their antiviral potential against HRoV [914, 27–29]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies demonstrate that plant extracts are deeply explored for their antiviral potential against HRoV [914, 27–29]. …”
Section: Discussionmentioning
confidence: 99%
“…One strategy is to explore plants as a source of novel active compounds due to the large structural diversity of natural products. Indeed, several studies reported on anti-HRoV activity by plant extracts [914]. In this context, we performed an antiviral screening of three plants endemic to Turkey flora and here we report on the anti-HRoV activity of Rindera lanata (Boraginaceae).…”
Section: Introductionmentioning
confidence: 92%
“…Water treatments with chlorine and synthetic flavonoids have been proven to impair the multiplication of human astroviruses [ 121 , 151 ]; the effect of natural extracts from the plant Achyrocline bogotensis [ 152 ] on astrovirus replication has also been demonstrated, but none of these compounds have been tested in vivo.…”
Section: Control and Preventionmentioning
confidence: 99%
“…In a Brazilian study, 4 species of medicinal plants were found to exhibit in vitro activity against rotaviruses [ 214 ]. In another in vitro study, fractions obtained from Achyrocline bogotensis were shown to exert a virucidal effect on rotaviruses and astroviruses, resulting in reduction of infectious viral particles [ 215 ]. Nutritional extracts of plants, such as Nelumbo nucifera Gaertn, Aspalathus linearis (Burm.f.)…”
Section: Rotavirus Therapeutics and Immunoprophylaxismentioning
confidence: 99%